2021
DOI: 10.1007/s10433-021-00618-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of formal volunteering that contribute to favourable psychological outcomes in older adults

Abstract: Although there is a large body of evidence documenting the benefits of engagement in formal volunteering among older people, research assessing the specific aspects of the volunteering experience that are associated with these benefits is limited. Accordingly, the objective of this study was to (i) examine the aspects of volunteering that predict improvements or declines in older people's psychological outcomes over time and (ii) assess the extent to which demographic characteristics and time spent engaging in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Merely joining volunteer organizations without a strong commitment did not appear to enhance well-being [ 23 ]. While the psychological beneficial effects of volunteering on well-being have been extensively documented [ 46 , 47 ], the present study revealed that for those who were already volunteering, engaging in formal volunteering five or more days per week, contributed to greater life satisfaction compared to those engaged in less than five days per week.…”
Section: Discussionmentioning
confidence: 48%
“…Merely joining volunteer organizations without a strong commitment did not appear to enhance well-being [ 23 ]. While the psychological beneficial effects of volunteering on well-being have been extensively documented [ 46 , 47 ], the present study revealed that for those who were already volunteering, engaging in formal volunteering five or more days per week, contributed to greater life satisfaction compared to those engaged in less than five days per week.…”
Section: Discussionmentioning
confidence: 48%
“…Ugyanakkor az önkéntesség típusa, helyszíne és az azt végző személy jellemzői is befolyásolják ezen hatásmechanizmust. Fontos azonban hozzátennünk, hogy számos kutatás eredménye utal arra is, hogy azok az idősebb önkéntesek, akik megbecsülést éreznek önkéntes munkájukért, és úgy vélik, hogy erőfeszítéseik hozzájárulnak mások jóllétéhez, nagyobb valószínűséggel számolnak be nagyobb szubjektív jóllétről, mint azok, akik nem érzik így (Jongenelis, Jackson, Warburton, Newton, & Pettigrew, 2022). Emellett az is látható, hogy negyven év fölött számottevően erősebb az önkéntesség és a jóllét kapcsolata, mint az azt megelőző életkori szakaszokban (Tabassum, Mohan, & Smith, 2016).…”
Section: Következtetések éS Javaslatokunclassified
“…The productive aging literature focuses on active engagement with life through volunteerism, continued vocational pursuits, and caregiving (Morrow-Howell & Greenfield, 2016). Volunteering is an activity associated with numerous positive psychosocial health outcomes among older adults, including an increased sense of purpose, life satisfaction, perceived growth (Jongenelis et al, 2021; Morrow-Howell & Greenfield, 2016; Pardasani, 2018), sense of purpose, self-rated health, self-esteem, quality of life, and decreased loneliness, isolation, depression, and functional limitations (Haski-Leventhal, 2009; Hong & Morrow-Howell, 2010; Jongenelis et al, 2021; Lee, 2022; Li & Ferraro, 2006; Morrow-Howell et al, 2003; Morrow-Howell & Greenfield, 2016; Narushima, 2005; Pardasani, 2018; Rozario, 2006; Tan et al, 2006). It is proposed that, similar to the benefits of paid work, volunteering may contribute to positive outcomes due to increased social, physical, and cognitive activity (Fried et al, 2004; Morrow-Howell & Greenfield, 2016).…”
Section: Introductionmentioning
confidence: 99%